2007
DOI: 10.1073/pnas.0610531104
|View full text |Cite
|
Sign up to set email alerts
|

Directing macromolecular conformation through halogen bonds

Abstract: The halogen bond, a noncovalent interaction involving polarizable chlorine, bromine, or iodine molecular substituents, is now being exploited to control the assembly of small molecules in the design of supramolecular complexes and new materials. We demonstrate that a halogen bond formed between a brominated uracil and phosphate oxygen can be engineered to direct the conformation of a biological molecule, in this case to define the conformational isomer of a four-stranded DNA junction when placed in direct comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

12
310
1
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 329 publications
(325 citation statements)
references
References 27 publications
12
310
1
2
Order By: Relevance
“…Among different noncovalent interactions, the halogen bond (X-bond) attracts particular attention of researchers because, similarly as the hydrogen bond (H-bond), it is responsible for physical, chemical, and biologic properties of a large group of chemical species [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16]. The X-bond is of the strength close to that of H-bond [1] and is strongly directional [17].…”
Section: Introductionmentioning
confidence: 99%
“…Among different noncovalent interactions, the halogen bond (X-bond) attracts particular attention of researchers because, similarly as the hydrogen bond (H-bond), it is responsible for physical, chemical, and biologic properties of a large group of chemical species [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16]. The X-bond is of the strength close to that of H-bond [1] and is strongly directional [17].…”
Section: Introductionmentioning
confidence: 99%
“…The specific role of halogen atoms in pinning a drug at the active site of the target enzyme via XB has been proven. In general, the role of XB in affecting binding and recognition phenomena between halogenated residues and biomacromolecules is attracting growing interest [26][27][28]. In this context, we have recently shown that the formation of halogen-bonded API-CCF cocrystals is a further opportunity offered by this interaction in biopharmacology [29,30].…”
Section: Introductionmentioning
confidence: 99%
“…Specific interactions between the halogen atoms (Cl, Br, I) of halogenated ligands and the electron pairs of oxygen/nitrogen/sulfur have been identified in many crystal structures of supramolecular ensembles [1][2][3] as well as in complexes between biomolecules and halogenated ligands [4][5][6][7][8]. In both cases this is based in part on the observation that the distance between a halogen atom and its electron-donating partner is significantly lower than the sum of their vdW radii ( Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…Statistical analysis showed that such halogen bonds exhibit a geometry similar to that of hydrogen bonds [4], including a directional preference. However, despite the clear evidence of short halogen-bonding contacts in many protein-ligand structures, their energetic contribution is still under active debate [2,6,[11][12][13][14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%